2015
DOI: 10.1001/jamainternmed.2015.1668
|View full text |Cite|
|
Sign up to set email alerts
|

Mediterranean Diet and Age-Related Cognitive Decline

Abstract: IMPORTANCE Oxidative stress and vascular impairment are believed to partly mediate age-related cognitive decline, a strong risk factor for development of dementia. Epidemiologic studies suggest that a Mediterranean diet, an antioxidant-rich cardioprotective dietary pattern, delays cognitive decline, but clinical trial evidence is lacking. OBJECTIVE To investigate whether a Mediterranean diet supplemented with antioxidant-rich foods influences cognitive function compared with a control diet. DESIGN, SETTING, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
456
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 729 publications
(509 citation statements)
references
References 47 publications
18
456
1
11
Order By: Relevance
“…This current piece of research followed some of the investigation categories that were identified in the Estruch et al, 2013;Valls-Pedret et al, 2015). Despite the positive effects of the Mediterranean diet on health having been cross-checked, studies evaluating dietary habits in Mediterranean countries confirm the change in Mediterranean eating behavior and show a shift towards an unhealthier type of diet (García-Closas et al, 2006;da Silva et al, 2009;Baldini et al, 2009;León-Muñoz et al, 2012;CIHEAM/FAO, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…This current piece of research followed some of the investigation categories that were identified in the Estruch et al, 2013;Valls-Pedret et al, 2015). Despite the positive effects of the Mediterranean diet on health having been cross-checked, studies evaluating dietary habits in Mediterranean countries confirm the change in Mediterranean eating behavior and show a shift towards an unhealthier type of diet (García-Closas et al, 2006;da Silva et al, 2009;Baldini et al, 2009;León-Muñoz et al, 2012;CIHEAM/FAO, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Además, la DMed tuvo un efecto favorable sobre el SM, mejorando sus componentes y disminuyendo su prevalencia por medio de un aumento en la reversión de esta condición con respecto al estado basal 40,41 . Finalmente, este mismo estudio PREDIMED demostró recientemente que esta dieta podría disminuir el deterioro cognitivo aso- ciado al envejecimiento 42 , así como la incidencia de cáncer de mama 43 . Todos estos beneficios asociados al consumo de una DMed fueron independientes de cambios en el peso corporal, lo que sugiere un efecto intrínseco -más allá de un ajuste del balance energético-de este patrón dietario 44 .…”
Section: El Estudio De Lyon Y La Iniciativa Predimedunclassified
“…The yielded results demonstrate unequivocally that adherence to the Mediterranean diet for a long period (6 years) impacts positively on memory slowing down significantly the cognitive decline vs control. Furthermore, the trial has shown a positive, specific, effect of EOO on frontal lobe function and on global cognitive function and a specific effect of nuts on different memory forms evaluated using a validated clinical test [11].…”
Section: Journal Of Anesthesia and Intensive Care Medicinementioning
confidence: 99%
“…In a recent study published in June 2015 in the prestigious Journal of the American Medical Association [11] for the first time 447 patients have been randomized and assigned to three arms: 157 have been assigned to Mediterranean diet added with known quantity of EOO, 147 to Mediterranean diet added with known quantity of nuts and 145 assigned to control diet; 127, 112 and 95 individuals, respectively, completed the study. Adherence to the diet has been confirmed by monitoring blood markers.…”
Section: Journal Of Anesthesia and Intensive Care Medicinementioning
confidence: 99%